WHIRLY1 is a major organizer of chloroplast nucleoids - Krupinska, Karin; Oetke, Svenja; Desel, Christine; Mulisch, Maria; Schäfer, Anke; Hollmann, Julien; Kumlehn, Jochen; Hensel, Götz (Frontiers in Plant Science, 2014)
WHIRLY1 is an abundant protein of chloroplast nucleoids, which has also been named pTAC-1 with regard to its detection in the proteome of transcriptionally active chromosomes (TAC). In barley primary foliage leaves, expression of the WHIRLY1 gene is highest at the base whereas protein accumulation is highest in the middle of the leaf where young developing chloroplasts are found. In order to elucidate the function of WHIRLY1 in chloroplast nucleoids, transgenic barley plants with an RNAi-mediated knock-down of the HvWHIRLY1 gene (RNAi-W1) were generated. The homozygous RNAi-W1-7 plants, barely containing traces of the WHIRLY1 protein, were chosen for detailed analyses of nucleoids. Nucleic acid specific-staining with YO-PRO®-1 revealed that in comparison to wild type chloroplasts, which have multiple small nucleoids attached to thylakoids, chloroplasts of the transgenic plants contain large irregularly formed patches of DNA besides nucleoids that are similar in size and shape to those of wild type chloroplasts. In large electron lucent areas filamentous structures were detected by conventional transmission electron microscopy. Analyses of ptDNA levels by both DNA dot-blot hybridization and quantitative PCR showed that leaves of the transgenic plants have a two- to threefold higher level of ptDNA than the wild type. The higher ptDNA level in RNAi-W1 plants coincided with an enhanced expression of the gene encoding a putative organelle targeted DNA polymerase in the mid part of primary foliage leaves. Furthermore, overexpression of the barley WHIRLY1 gene in E. coli cells revealed a higher compaction of bacterial nucleoids. These results suggest that WHIRLY1 belongs to the group of plastid nucleoid associated proteins (ptNAP) having a function in compacting a subpopulation of chloroplast nucleoids thereby affecting DNA replication.